PENERJEMAHAN GAYA BAHASA UTAKATA NO KI KARYA MORI OGAI - Widiyana, Hanifah; Widiati, Sri Wahyu; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to describe the method and procedure of the language style translation in Mori Ogaiâ€Ÿs short story titled â€œUtakata No Kiâ€. This short story has been translated by Bambang Wibawarta entitled â€œCatatan Buih di Atas Kertasâ€ at 2003. The method used in this reseach is qualitative descriptive and used theory of Newmark (1988) and Gorys Keraf (1980). The method of data collection used is technical notes. The result of this research are 40 data style of language, containing simile 8 data, simile and personification 1 data, the metaphor 2 data, the personification 5 data, the eponymous 2 data, the eponymous and cynicism 1 data, sinekdoke 1 data, antonomasia 1 data, irony 2 Data, cynicism 4 Data, sarcasm 6 data, and satire 3 data. The style of language translation used various translation methods, wich are communication, faithful, free, adaptation, and semantics. The procedures used are component analysis, shift or transposition, reduction, expansion, cultural equivalence, modulation, synonyms. Then, the result of research showed that the translator uses the closest equivalent in target language. The aim is make the message from the authors delivered well by the translator. Although there is a shift in meaning or form, but can be the shift is made to produce acceptable translations according to the readers.Keywords: Translation, style of language, Utakata No Ki